Correlation of the expression of tumor necrosis factor-alpha in chronic periapical lesions with the expression of bacterial chaperonin 60 - Stanišić Zindović, Jelena; Mihailović, Branko; Djordjević, Filip; Milovanović, Marija; Arsenijević, Nebojša; Milovanović, Jelena; Acović, Aleksandar; Dubovina, Dejan (Vojnosanitetski pregled, 2022)
Background/Aim. Chronic microbial infections of the root canal are a common issue. This process very often causes an immune reaction in the root canal system that results in forming of chronic periapical lesions (PLs). The aim of this study was to determine the quantitative expression of the bacterial heat shock protein (HSP), chaperonin 60 (cpn60), and the pro-inflammatory and anti-inflammatory cytokines in periapical tissue obtained from individuals with chronic PLs and to determine if there is a correlation between the expression of the bacterial HSP and the expression of these cytokines. Methods. The study was performed on 18 PLs and 6 control samples of healthy periapical tissue, taken at the Department of Dentistry, Faculty of Medicine, University of Priština/Kosovska Mitrovica. The levels of messenger ribonucleic acid (mRNA) expression of pro- and anti-inflammatory cytokines and bacterial HSP were determined by quantitative real-time polymerase chain reaction (RT-PCR) and quantified by comparing to the internal control gene for glyceraldehyde 3-phosphate dehydrogenase (GAPDH). Results. Analysis revealed significantly higher mRNA levels of tumor necrosis factor-alpha (TNF-a) and cpn60 in the tissue of PLs compared with normal periapical tissue (p < 0.05). Contrary to these results, the mRNA expression of anti-inflammatory interleukin-10 (IL-10) was significantly higher in the samples of normal periapical tissue compared with the mRNA levels of this cytokine in the tissue of PLs (p < 0.001). Expression of cpn60 is in strong correlation with TNF-a expression in PLs. Conclusion. cpn60 released from bacteria in periapical tissue could be a strong stimulator of inflammatory response and one of the important players in the pathogenesis of PLs.